Are U.S. clinical trial sites in the right places to meet the demand for the population density of those over 60?: Epidemiology / Prevalence, incidence, and outcomes of MCI and dementia. (7th December 2020) - Stanton, Sean; Dwyer, John; Ward, Nichol; Vradenburg, George; Taylor, James
Abstract: Background: There are approximately 31 drugs in phase 3 and 68 drugs in phase 2 development for memory impairment. It is reported that there are approximately 200 sites in the US that are capable of randomizing 25 subjects per year. The current demand for participants is approximately 25, 277 across 55 studies requiring this type of enrollment. That means we would need approximately 505 clinical trials sites capable of randomizing at least 25 subjects per year. Is it possible to meet this demand? Prior to answering this question we researched where in the US the population is located for people >60 years of age. We also researched where clinical trial sites were in relation to this population. And lastly, how many of these sites have done at least 1 memory study in the last 2 years. To determine if the US has sites positioned in the right places to meet the demand from both the patient and the industry/NIH for Alzheimer's disease. If yes, can we increase capacity to meet the patient enrollment needs? If no, what do we need to do organically to grow sites to meet this demand. Method: The population was surveyed using the US Census and plotted graphically using. The data can be seen in the graphs. Data on the site locations was compiled though clinical trials.gov. The data on Alzheimer's sites was also collected from ClinicalTrials.Gov. The data on the Global Alzheimer's Sites was supplied by GAP. Each data set has scatter plot Result: The results are plotted on the graphs below. Conclusion: The site locations do not align cohesively with the population greater the 60 years of age. As the demand of subject enrollment increases there is further pressure on existing sites within overly saturated clinical trial site zones while other zones offer no clinical trial sites within 50 miles. This will continue to lead to low performance and delayed timelines. We will offer answers to expanding site capabilities, organically growing zones in void of clinical trial sites, and also teaching sites interested in stopping Alzheimer's the dynamics to being successful in clinical trials for Alzheimer's Disease.